Production of Antibacterial Activity and Bone Cell Proliferation by Surface Engineering of Ga‐ or Mn‐Doped Ceria‐Coated Biomedical Titanium Alloy. Issue 10 (8th May 2022) - Khosravanihaghighi, Ayda; Koshy, Pramod; Yasir, Muhammad; Romanazzo, Sara; Lovric, Vedran; Kilian, Kristopher Alan; Willcox, Mark Duncan; Walsh, William Robert; Sorrell, Charles Christopher
Abstract : The present work reports a detailed interpretation of the role of Ga and Mn dopants, solid solubility mechanisms, charge compensation mechanisms, intervalence charge transfer, antibacterial performance, and cell attachment and proliferation. Sol–gel undoped and doped (1, 5, and 9 mol%) CeO2 films are spin‐coated on 3D printed Ti6Al4V biomedical alloy substrates and annealed at 650 °C for 2 h in air. Material characterization includes scanning electron microscopy (SEM), 3D scanning laser confocal microscopy, glancing angle X‐ray diffraction (GAXRD), and X‐ray photoelectron spectroscopy (XPS). In vitro testing includes inhibition of bacterial growth, simulated body fluid (SBF) testing, and cell attachment and proliferation studies. The most significant outcome is that the bioactivity of ceria derives directly from the Ce 3+ concentration, which itself results from solid solubility (substitutional and interstitial) and charge compensation and redox. This challenges the common assumption of the dominance of oxygen vacancies in the performance of ceria. The antibacterial activity is dependent on the type, amount, and valence of the dopant, where opposite trends are observed for gram‐positive Staphylococcus aureus and gram‐negative Escherichia coli bacteria. All of the doped samples result in enhanced cell proliferation, although this is greatest at the lowest dopant concentration. Surface hydroxyapatite formation on the samples is achieved by soaking in SBF at 2 weeks and 1 month. Abstract : The bioactivity of ceria derives directly from the Ce 3+ concentration, which itself results from solid solubility (substitutional and interstitial) and charge compensation and redox. This challenges the common assumption of the dominance of oxygen vacancies in the performance of ceria. All of the doped samples result in enhanced cell proliferation, although this is greatest at the lowest dopant concentration.